Export boom, employment bust? The paradox of Indonesia's displaced workers, 2000-2014 - Rashesh Shrestha; Ian Coxhead (Asian Development Bank Institute (ADBI), 2018)
In Indonesia, an export boom and rapid, sustained gross domestic product (GDP) growth in the decade after 2000 was accompanied by real earnings that were flat on average, and even declined for many workers. Conventional models of growth and trade predict that labor productivity rises as an economy develops; that this should not be observed during a period of high GDP growth is a puzzle that merits careful investigation. In this paper we explore these seemingly paradoxical trends using several waves of a panel of individual employment data. Economic growth is rarely balanced in a sectoral sense, and the nature of the structural change experienced by Indonesia is also strongly associated with lower competitiveness in sectors in which formal employment rates are high, causing some degree of involuntary labor movement from formal to informal modes of employment. We explore this econometrically and find that the earnings of workers displaced from formal to informal jobs are significantly lower than those of workers who remain in the formal market. The fact of this displacement, and its implications for individual earnings, undercuts conventional thinking about the welfare gains from a sustained growth experience. Our findings add, perhaps for the first time, a developing country dimension to the existing job displacement literature. They also shed some light on the causes of Indonesia's unprecedented increase in inequality during the same growth period.
Keywords: E24; F16; J23; J46; J63; O17; 330; displacement; formal; informal; earnings; Indonesia